Growth of Barbus xanthopterus(Heckel) Juveniles Under Laboratory Conditions - Farnar, Khalid William (Iraqi Journal of Aquaculture, 2022)
The growth of Barbus xanthopterus (Heckel) juveniles was studied with men primary length and weight 7.96±0.076 cm 37.14±0.032 gm respectively in aquariums under laboratory conditions using artificial diet for a period sixty days, the biological parameters, length, weight, weight increase, relative growth rate, specific growth rate and some environmental parameters were also measured. The environmental parameters was within the ideality limit of Barbus xanthopterus, the results showed the existence of differences in growth rates between fishes in aquariums experience the highest rate for increasing weight recorded for fish in the aquarium B, amounting to 118.4 g, followed by the fishes in the aquarium A and B, amounting to 114.6 and 111.2 g respectively. The study showed that the current fish Barbus xanthopterus is a local fish that can be cultivated because they give great growth encouraging compete with local species other if cultured in appropriate environments and densities because the growth is directly proportional to the temperature, the total values for increasing weight (every 15 days) during the experiment was 0.832and 1.383 and 1.350 and 1.606 g / day.